Fourth graders' adaptive strategy use in solving multidigit subtraction problems. (June 2020) - Hickendorff, Marian
Abstract: Using the choice/no-choice methodology we investigated Dutch fourth graders' ( N  = 124) adaptive use of the indirect addition strategy to solve subtraction problems. Children solved multidigit subtraction problems in one choice condition, in which they were free to choose between direct subtraction and indirect addition, and in two no-choice conditions, in which they had to use either direct subtraction or indirect addition. Furthermore, children were randomly assigned to mental computation, written computation, or free choice between mental and written computation. One third of the children adaptively switched their strategy according to the number characteristics of the problems, whereas the remaining children consistently used the same strategy. The likelihood to adaptively switch strategies decreased when written computation was allowed or required, compared to mandatory mental computation. On average, children were adaptive to their own speed differences but not to the accuracy differences between the strategies. Highlights: Fourth graders used indirect addition frequently and efficiently. The majority of the children consistently used one strategy. One-third of the children were adaptive to the problem's number characteristics. Children fit their strategy choice to speed but not to accuracy advantages. Requiring either mental or written computation affects strategy adaptivity.